Spontaneous conversion of atrial fibrillation caused by severe hyperkalemia: A case report. Issue 15 (April 2018) - Yan, Lihua; Jiang, Tingbo; Yang, Xiangjun; Xu, Mingzhu
Abstract: Rationale: Hyperkalemia is a life-threatening electrolyte disturbance which could lead to arrhythmias and potentially death. Patient concerns: An 82-year-old male patient who presented typical electrocardiographic indications of hyperkalemia, including the absence of P waves, prolongation of QRS complex, sinoventricular conduction, bradyarrhythmia and tall peaked T waves. He developed a rare self-defibrillation of atrial fibrillation to sinus rhythm due to hyperkalemia. Besides, he developed secondary thrombosis caused by abrupt termination of atrial fibrillation. Diagnoses: This patient was diagnosed with hyperkalemia, hypertension, and AF. Interventions: He was treated with an intravenous infusion of calcium gluconate, insulin and dextrose, an oral kayexalate, and emergency hemodialysis. Outcomes: The patient was managed effectively and discharged with stable status. Lessons: Hyperkalemia could induce malignant arrhythmia with high mortality. Thus we suggested more attention be paid to monitoring electrolyte disorders and maintaining anticoagulation treatments to avoid thromboembolism.